Characterization and identification of sources of rust resistance in Triticum militinae derivatives - Chowdhury, Saikat; Bansal, Shreshtha; Jha, Shailendra K.; Saharan, M. S.; M., Niranjana; K., Raghunandan; Choudhary, Manish K.; Agarwal, Priyanka; Mallick, Niharika; Vinod (Scientific reports, 2024)
Triticum militinae (2n = 4X = 28, A t A t GG), belonging to the secondary gene pool of wheat, is known to carry resistance to many diseases. Though some disease resistance genes were reported from T. timopheevii, the closest wild relative of T. militinae, there are no reports from T. militinae. Twenty-one T. militinae Derivatives (TMD lines) developed at the Division of Genetics, IARI, New Delhi, were evaluated for leaf and stripe rusts at seedling and adult plant stages. Eight TMD lines (6–4, 6–5, 11–6, 12–4, 12–8, 12–12, 13–7 and 13–9) showed seedling resistance to both leaf and stripe rusts while six TMD lines (7–5, 7–6, 11–5, 13–1, 13–3 and 13–4) showed seedling resistance to leaf rust but adult plant resistance to stripe rust and three TMD lines (9–1, 9–2 and 15) showed seedling resistance to leaf rust but susceptibility to stripe rust. Three TMD lines (2–7, 2–8 and 6–1) with adult plant resistance to leaf and stripe rusts were found to carry the known gene Lr34/Yr18 . Ten TMD lines (7–5, 7–6, 9–1, 9–2, 11–5, 11–6, 12–12, 12–4, 12–8, and 15) with seedling resistance to leaf rust, showing absence of known genes Lr18 and Lr50 with linked markers requires further confirmation by the test of allelism studies . As not a single stripe rust resistance gene has been reported from T. militinae or its close relative T. timpopheevii , all the 8 TMD lines (6–4, 6–5, 11–6,12–4, 12–8, 12–12, 13–7 and 13–9) identified of carrying seedling resistance to stripe rust and 3 TMD lines (13–1, 13–3 and 13–4) identified of carrying adult plant resistance to stripe rust are expected to carry unknown genes. Also, all the TMD lines were found to be cytologically stable and thus can be used in inheritance and mapping studies.